Valsts prezidenta un Saeimas savstarpējās attiecības. - Ūsiņš, Mikus (Latvijas Universitāte, 2011)
Bakalaura darbā „Prezidenta un Saeimas savstarpējās attiecības” tiek apkopotas Latvijas Valsts prezidenta un Saeimas savstarpēji saistītās tiesības, pienākumi un pilnvaras, to izcelsme un normatīvais regulējums Latvijas Republikā. Skatītās attiecības tiek sadalītas pēc to mērķa un Latvijas Valsts prezidenta un Saeimas līdzdalības to īstenošanā. Pamatojoties uz darbā izmantotajiem Latvijas tiesību aktiem, tiek skatīta attiecību veidošanās, būtība un apmēri Latvijas tiesību sistēmā, kā arī to atbilstība demokrātiskas republikas pamatprincipiem. Darba rezultātā tiek noskaidrotas attiecību dažādās izpausmes, problemātika, kā arī Valsts prezidenta un Saeimas institūciju savstarpējā nepieciešamība un saikne ar savas varas avotu.

The bachelor thesis covering „The Relations Between the President and Saeima” summons the interrelations between the rights, responsibilities and the power granted to the president and the parliament of Latvia – the Saeima. The thesis investigates the historical background and the regulatory framework in the Republic of Latvia of both institutions.The relations are divided by their aim and the role of execution by the president and Saeima. Based on the legislation of Latvia, the formation of relations are examined by their essence, volume on the background of the legal system of Latvia, as well as their conformity wih the basic principles of a democratic republic. The main conclusions show the diverse relations, related problems and discrepancies, as well as the mutual necessity of both instances – the president and Saeima, and the link with the source of their power.
The relations between President and Saeima.
Keywords: Juridiskā zinātne